2020
DOI: 10.1021/acs.analchem.0c01558
|View full text |Cite
|
Sign up to set email alerts
|

Polarized-Electrochemiluminescence Biosensor Based on Surface Plasmon Coupling Strategy and Fluorine-Doped BN Quantum Dots

Abstract: The first polarized-electrochemiluminescence (ECL) biosensor is reported in this work. Surface plasmon coupling ECL (SPC-ECL) strategy is developed for the amplified polarization light of fluorine-doped BN quantum dot (F-BN QD) emitters. The generation of polarized-ECL is attributed to the characteristic of polarization-angle-dependent SPC effect. A polarized sandwich-type biosensor based on F-BN QDs and Au nanoparticles (Au NPs) is established to detect the K-ras gene. The polarized-ECL sensor is more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The solvothermal process can produce BN materials, such as BN quantum dots, which are difficult to obtain by other methods. [54,55] As depicted in Figure 3e, BN quantum dots with controllable sizes can be generated by the hydrothermal reaction from a mixed solution of H 3 BO 3 and NH 3 above 200 °C. [54] The results show that the average size of BN is 2.56 nm after 9 h of reaction between the B source and N source with a mole ratio of 1:4, and it changes to 3.20 nm after 15 h. Ma and coworkers used H 3 BO 3 , C 3 H 6 N 6 , and NH 4 F as raw materials to synthesize F-doped BN quantum dots by a microwave-assisted hydrothermal synthesis.…”
Section: Liquid Phase Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The solvothermal process can produce BN materials, such as BN quantum dots, which are difficult to obtain by other methods. [54,55] As depicted in Figure 3e, BN quantum dots with controllable sizes can be generated by the hydrothermal reaction from a mixed solution of H 3 BO 3 and NH 3 above 200 °C. [54] The results show that the average size of BN is 2.56 nm after 9 h of reaction between the B source and N source with a mole ratio of 1:4, and it changes to 3.20 nm after 15 h. Ma and coworkers used H 3 BO 3 , C 3 H 6 N 6 , and NH 4 F as raw materials to synthesize F-doped BN quantum dots by a microwave-assisted hydrothermal synthesis.…”
Section: Liquid Phase Synthesismentioning
confidence: 99%
“…[54] The results show that the average size of BN is 2.56 nm after 9 h of reaction between the B source and N source with a mole ratio of 1:4, and it changes to 3.20 nm after 15 h. Ma and coworkers used H 3 BO 3 , C 3 H 6 N 6 , and NH 4 F as raw materials to synthesize F-doped BN quantum dots by a microwave-assisted hydrothermal synthesis. [55] In addition, using graphene oxide (GO), H 3 BO 3 , and different N sources as precursors (urea and NH 3 ), Kuila and co-workers realized the hydrothermal preparation of BN and a reduced GO (rGO) heterojunction. [56,57] Compared with that of the insulating h-BN, the electronic band of this superlattice is improved, making the electrical conductivity of the as-obtained BN increase significantly.…”
Section: Liquid Phase Synthesismentioning
confidence: 99%
“…The authors further reported on the use of S-regulated BNQDs along with AuNPs with higher ECL performance for BRAF gene detection and quantification using the same SPC-ECL strategy as discussed above [75]. Further, Liang et al [104] reported the first polarized-ECL biosensor developed using SPC-ECL strategy and fluorine-doped BNQDs to detect the K-ras gene. The fluorine-doped BNQDs ECL signal was reported to be enhanced at a specific polarization angle, thanks to polarization angle-dependent SPC-ECL.…”
Section: Electrochemiluminescence (Ecl) Responsesmentioning
confidence: 99%
“…Professor Francesco Zinna and his co-workers obtained highly circularly polarized ECL signals through pure organic molecules . In our previous work, we observed the polarization characteristics of surface plasmon-coupled ECL (SPC-ECL) . The isotropic emission of quantum dots (QDs) was converted into enhanced and directional emission through interaction with Au NPs because there was a pairing between the metal plasmon and the QD exciton when the luminescent material was close to the surface of the metal nanoparticle or nanofilm.…”
mentioning
confidence: 94%